RESTORING VISION IN CENTRAL MACULAR EDEMA (CME) CAUSED BY CENTRAL RETINAL VEIN OCCLUSION (CRVO): SINGLE INTRAVITREAL BEVACIZUMAB INJECTION - Iskandar, Ferdy; Pertiwi, Adinda Mulya; Hutapea, Mario Marbungaran (Indonesian Vitreoretinal Society, 2025)
Introduction: Central retinal vein occlusion (CRVO) stands as a prevalent contributor to vision impairment from retinal vascular issues, affecting approximately 0.08% of individuals over 30. Cystoid macular edema (CME) is the most frequent cause of reduced vision among these cases. This study aimed to report the promising outcome of a single intravitreal bevacizumab injection in treating CME secondary to CRVO. Case Report: A 41-year-old male came with a sudden blurry vision of the left eye (LE) 10 hours before admission, particularly in the superior and temporal areas. He denied any history of red eyes, sudden light flashes, curtain-like shadows, double vision, or pain with eye movements. He had a history of hypertension but was not on medication. His blood pressure was 180/120 mmHg, with visual acuity (VA) of 1/60, positive relative afferent pupillary defect (RAPD), edematous optic nerve head (ONH) with tortuous veins, and hemorrhages throughout the retina of the LE. Macular optical coherence tomography (OCT) of the LE showed massive intraretinal fluid (IRF) with a central macular thickness (CMT) of 779 µm. He had unremarkable laboratory results, with normal coagulation factors. Amlodipine 10 mg once daily (qd) and candesartan 16 mg qd was prescribed, and no antiplatelet or anticoagulant therapy was initiated by the internal medicine. A single intravitreal bevacizumab injection (1.25mg) was performed on the LE. During a 1-month follow-up, his best corrected visual acuity (BCVA) improved to 6/18, with a normal optic nerve head, tortuous veins, flame-shaped hemorrhages, with no IRF and a CMT of 240 on macular OCT. The BCVA and CMT remained stable at the 6-month follow-up, with no complications. Discussion: A Treat and extend (T&E) regimen was initially planned, with ≥ 3 consecutive monthly injections until disease inactivity was established, followed by a gradual extension of the treatment interval in increments of 2 to 4 weeks. We initially planned to administer bevacizumab intravitreal injections according to the T&E regimen. However, the patient showed significant clinical improvement, and macular OCT demonstrated resolution of the IRF after the first injection. Therefore, we decided to discontinue the remaining injections and switch to a pro re nata (PRN) approach, administering bevacizumab as needed. In real-life conditions, the number of anti-vascular endothelial growth factor (VEGF) injections was lower than in randomized controlled trials (RCTs), due to many factors, such as declining motivation after improvement, poor access to hospital facilities, and unaffordable travel expenses. The PRN regimen is also a good option to minimize costs and reduce the burden on both patients and healthcare providers. Conclusion: Single intravitreal bevacizumab is an effective treatment for CME secondary to CRVO. However, the decision to use the T&E and PRN regimen should be based on the patient’s improvement and clinical examination. Additionally, any systemic conditions related to the vascular condition must also be addressed and treated.